Indonesian Millennials Inside the Vortex of Identity Politics - Eryan Ramadhani (WIMAYA, 2020)
Indonesia has long historical relations with China. The Chinese—mostly merchants— arrived much earlier than the Dutch, although no written records are available as to the exact date of their arrival. After Indonesia proclaimed independence in 1945, the Chinese found themselves in a precarious position. The anti-China narrative was played up to bolster the impression that the pribumi was somewhat threatened. This article centers on the use of anti-China narrative in election campaigns, surveys on millennial voting behavior and political preferences. It aims to provide descriptive explanation of how Indonesian millennials are contextualized within domestic political constellation, focusing on the use of identity politics in election campaigns.